QADRIYAT TUSHUNCHASINING TUZILISHI VA UNING MAZMUNI - Rahmonova Nilufar Najmiddin qizi, Yuldoshev Tojiddin Abdukarimovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The elimination of conflict situations between families is one of the urgent problems in the world, and comprehensive scientific research is being conducted on the issues of developing mechanisms based on moral values to eliminate the negative consequences arising from them.